High altitude reduces infection rate of COVID-19 but not case-fatality rate - Segovia-Juarez, Jose (2020)
Coronavirus disease 19 (COVID-19) is a pandemic caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). It is suggested that life at high altitude may reduce COVID-19 infections and case-fatality rates (cases/deaths). We study data from Peru COVID-19 pandemics, which first case was recorded on March 6th, 2020. By June 13, 2020 there were 6498 deaths, and 224,132 SARS-CoV-2 positives. Using data from 185 capitals of provinces with altitudes ranging from 3 to 4342 m, we confirm previous reports that infection with COVID-19 at high altitude is reduced. However, case-fatality rate is not dependent of altitude. We have also presented first evidence that female protection towards death by COVID-19 is reduced as altitude of residence increases. © 2020 Elsevier B.V.